Aboriginal Communities of the Northern Territories: Traditional Aboriginal Medicines in the Northern Territories of Australia & ’Lummo’: Rabbit on a Shovel & Ian Bersten: Coffee Floats Tea Sinks & Aïda Kanafani-Zahar: Mune- La conservation alimentaire traditionelle au Liban & Gillian Riley: (1) Renaissance Recipes, (2) Impressionist Picnics, and (3) The Dutch Table & Joop Witteveen (ed): lndisch Kookboek door eene lndische dame (facsimile reprint) - Davidson, Alan E (Petits Propos Culinaires, 1994)
Aboriginal Communities of the Northern Territories: Traditional Aboriginal Medicines in the Northern Territories of Australia: Conservation Commission of the Northern Territory, Darwin, 1993: ISBN 0 7245 2711 7: 674 pp, numerous b/w drawings plus colour photographs, glossary, bibliography, index, AUS90 (+ AUS40 postage for international airmail): to order, telephone INT’L + 61 89 894 529 or fax INT’L + 61 89 323 849 or write to Records, CCNT; PO Box 496; Palmerston NT 0831; Australia - and ask about their smaller publications on aboriginal uses of food plants etc etc. ’Lummo’: Rabbit on a Shovel: Primavera, Leichhardt, Sydney: ISBN 1 875368 07 8: 190 pp, b/w drawings, table of contents doubles as index, price not stated (won’t be much). Ian Bersten: Coffee Floats Tea Sinks: Helian Books, Sydney, 1993: ISBN 0 646 09180 8: 284 pp (format a shade bigger than A4), almost innumerable colour and b/w illustrations, bibliography, index, AUS140 (price in UK £60.00, UK distributor Helian Books, PO Box 4, Radlett, Herts WD7 7JT, fax/phone 0923 857 150: US price 90.00 + shipping- try the Coffee Bean, 1630A West Evans, Englewood CO 80110). Aïda Kanafani-Zahar: Mune- La conservation alimentaire traditionelle au Liban: Editions de la Maison des sciences de l’homme, Paris, 1994: ISBN 2 7351 0539 3: 280 pp, numerous b/w drawings and a section of colour photographs showing women working on the preservation of foods, glossary, bibliography, no index (but full table of contents), paperback, 195 French francs. Gillian Riley: (1) Renaissance Recipes, (2) Impressionist Picnics, and (3) The Dutch Table: Pomegranate Artbooks, Rohnert Park CA, 1993: (1) ISBN 1 56640 577 7, (2) ISBN 1 56640 580 7, (3) ISBN I 56640 978 0: 96 pp each, many colour reproductions of paintings, bibliography, index, £12.95 in the UK. Joop Witteveen (ed): lndisch Kookboek door eene lndische dame (facsimile reprint): de Kan, Amsterdam, 1994: ISBN 90 801201 4 6: 118 pp, including added introduction by Joop Witteveen and glossary, 19 Dutch guilders (add 3 guilders for postage and order from de Kan, Binnenkadijk 237, 1018 ZG Amsterdam).